2007
DOI: 10.1159/000108369
|View full text |Cite
|
Sign up to set email alerts
|

Tonsillectomy Techniques and Pain: A Review of Randomized Controlled Trials and Call for Standardization

Abstract: Objectives: To review the literature comparing operative techniques in tonsillectomy and postoperative pain. Methods: Randomized controlled trials comparing operative techniques and pain outcomes over a 10-year period were reviewed. Results: 44 trials met inclusion criteria for analysis. A total of nine different techniques for complete or partial tonsillectomy were compared. There were several studies with contradictory results. Many of the studies were performed under different parameters. Conclusions: Futur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 125 publications
0
17
0
Order By: Relevance
“…A variety of methods have been attempted to reduce posttonsillectomy pain, including various surgical techniques, newly developed devices producing low heat and temperature, local or systemic steroid administration, local anesthetic blocks, and use of analgesics [9][10][11][12][13]. Generally, surgical techniques and devices influence postoperative pain more than pharmacologic intervention.…”
Section: Discussionmentioning
confidence: 99%
“…A variety of methods have been attempted to reduce posttonsillectomy pain, including various surgical techniques, newly developed devices producing low heat and temperature, local or systemic steroid administration, local anesthetic blocks, and use of analgesics [9][10][11][12][13]. Generally, surgical techniques and devices influence postoperative pain more than pharmacologic intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that the technique of tonsillotomy decreases the risk of post-operative haemorrhage 12 and the duration and severity of post-operative pain by over 50 per cent, compared with tonsillectomy. 13,14 In tonsillotomy, the tonsillar capsule is not breached and the underlying muscle is protected, resulting in less pain. Ericsson 15 and Hultcrantz 16 found that children younger than 15 years with tonsillar hypertrophy, both with and without recurrent infection, benefitted from less invasive tonsillar surgery, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study attempted a similar analysis, however, the authors limited their study to tonsillectomy techniques and pain [81]. They also conclude that standardized protocols are needed for useful comparison.…”
Section: Outcome Measuresmentioning
confidence: 99%